Talinum Triangulare como substrato alternativo para bebida tipo Kombucha - SILVA, Mauriane Maciel da (2022)
The kombucha beverage has become a presence on food trend each year. Although black and green teas are the substrates traditionally used in their production, research has been carried out using infusions of different plants. Thus, the aim of this study was to develop fermented kombucha beverages from leaves and unconventional joão-gomes (Talinum triangulare) parts as alternative substrates. For this, the study was divided into four stages. Initially, a survey of the profile of potential kombucha consumers was carried out. In the second stage, the growth conditions of microorganisms in tea made from leaf (LJG) and stem (SJG) flour from joão- gomes were evaluated. In the third stage, the growth kinetics of microrganisms of the best formulations on days 0, 2, 4, 6, 8 and 10 were evaluated. Determinations of microorganism enumeration and pH were performed. In the fourth stage, the beverage was flavored with grape juice. For this stage, LJG, SJG and mixed beverages (containing LJG and SJG) were produced, which were compared with the traditional beverage of green tea. The beverages were divided into 3 treatments: unfermented, fermented and fermented and flavored. The determinations performed were microrganisms enumeration, total phenolics, total flavonoids, antioxidant activity, pH, volatile acidity, alcohol content and color. At this stage, the sensory evaluation of the beverages was also carried out. According to the results, it was possible to characterize the consumer profile and define the buyer persona for the beverage. The optimal conditions for the production of beverages from LJG were 5.09% flour and 7.46% sucrose. For beverages obtained from SJG, 2.14% flour and 6.05% sucrose were used. Fermentation for 8 days at 30 °C provided the highest viability of acetic and lactic bacteria and yeasts. Phenolic compounds and antioxidant activity increased with the fermentation and flavoring of the beverages. For the the physicochemical characteristics, the pH values, volatile acidity and alcohol content were in accordance with the identity and quality standards established in Brazilian legislation and the alcohol content values characterize the drinks as non-alcoholic. For the color, in fermented and flavored beverages, grape juice provided a product with less lightness and greater redness. For the sensory evaluation, beverages containing leaves had high percentages in the not enough region, so there was a rejection of the beverage. However, stems and mixed drinks were well accepted. Thus, LJG and SJG are good substrates for the production of kombucha drinks, with stem and mixed drinks having better acceptance.